Pengaruh Religiusitas Diri dan Orangtua terhadap Kebahagiaan Remaja - Rini, Rini (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
Religiosity has an important role in shaping teenage happiness. Belief in God can bring peace that brings happiness. In addition, having parents who are also religious can make teenagers feel more calm in parenting and feel happy. This study has two objectives, to determine the effect of religiosity on teenage happiness and the influence of parental religiosity on teenage happiness. The respondents of this study were 464 teenagers, with accidental sampling technique. Data is collected by google forms which are distributed via WhatsApp, Telegram, Facebook, and email. Data analysis using linear regression. The results showed that religiosity positively influenced and significantly related to teenage happiness, and parental religiosity positively influenced and significantly related to teenage happiness. Also, parental religiosity positively influenced and significantly related to teenager religiosity.